Experimental study of a photovoltaic direct current water pumping system for irrigation in rural-isolated Region of Arequipa, Peru - Peralta Vera, Aixa Anel (2019)
In the present experimental study, a photovoltaic (PV)-powered system in continuous current (4 kW) for the pumping of water in an isolated, rural agricultural zone in Arequipa—Peru was analyzed. A meteorological station was installed in the studied zone, measuring solar radiation, temperature, relative humidity, and wind speed. The electrical and hydraulic parameters of the solar-pumping system (i.e., electric current, voltage, mass flow, and hydraulic pressure) were measured in order to evaluate the efficiency of the energy transformation processes. The results indicate that, during the year of 2017, the PV pumping system in direct current (DC) functions from 07 h 30 min to 15 h 30 min, during an average of 8 h a day. The PV array, hydraulic, and global efficiencies were evaluated. This allows for the interpretation of efficiency independent of solar irradiance. The efficiency of the PV array and global efficiency remained constant (11.5% f and 8.5%, respectively). The functioning interval of the PV array ranges from 880 W up to 3400 W, making evident the versatility of the system of generation and consumption in DC, which is able to function since solar irradiance is at least 200 W/m2, corresponding to 880 W of PV array power, 27 m of total dynamic head (TDH) and 2 kg/s of mass flow,and 70% hydraulic efficiency. With greater mass flows (6.3 kg/s), the PV array power was 3256 W with a hydraulic efficiency of 55%, a TDH of 30 m, and a peak solar irradiance of 1190 W/m2. When the whole system functions in DC, the efficiencies are superior to those of systems, which operate with DC/alternating current (AC) current inverters